The Penang Libraries Past, Present & Future - Fazal, Anwar (Persatuan Pustakawan Malaysia, 2015)
This paper is based on a presentation made at The Penang Story Seberang Perai Lecture held at the Penang Public Library Corporation, Seberang Perai, Penang on 23 November 2015, organised by the Penang Heritage Trust (PHT) and sponsored by Think City Sdn. Bhd. It looks at the development of libraries in Penang over the years.